Identification of tRNA-derived RNAs in adipose tissue from overweight type 2 diabetes mellitus patients and their potential biological functions - Zhang, Jie; Xi, Yingfei; Fei, Qiuping; Xu, Jun; Hu, Jinxing (Frontiers in Endocrinology, 2023)
Background: Type 2 diabetes mellitus (T2DM)causes a huge public health burden worldwide, especially for those who are overweight or obese, the pain is often greater. And search for effective targets in overweight T2DM could help improve patient quality of life and prognosis. tRNA-derived RNAs (tsRNAs) are multifunctional regulators that are currently receiving much attention, but there is still a lack of knowledge about tsRNAs in overweight T2DM. Methods: T2DM patients with BMI ≥ 25 (Overweight group) and BMI < 25 (Control group) were subjected to tsRNA sequencing; differentially expressed tsRNAs in the two groups were analyzed and their expression was verified using qRT-PCR. The biological function of downstream target genes was also evaluated by enrichment analysis. Results: qRT-PCR evaluation identified a tsRNA with up-regulated expression (tRF-1-28-Glu-TTC-3-M2) and a tsRNA with down-regulated expression (tRF-1-31-His-GTG-1), both of which may be involved in metabolic and energy-related processes. Conclusion: Dysregulation of tsRNA expression in overweight patients with T2DM suggests a potential role for tsRNA in the development of T2DM.